Hypothesising a simpatico relationship between multiculturalism and religious extremism : the case of Singapore - Poh, Rachyl Wan Ting (2019)
The concept of ‘multiculturalism’ may have been the bane of Angela Merkel, David Cameron and Nicolas Sarkozy’s political terms, but it is one of the very few ideas that receives bipartisan consensus and has been hailed as a bulwark against terror in Singapore. This dissertation commences by calling for multiculturalism to be taken off its pedestal and probes into a possible simpatico relationship between multiculturalism and religious extremism. In doing so, the dissertation first peruses current literature to reveal the lack of meaningful research performed on the possible correlations between these two concepts in Singapore. Thereafter, using insights obtained from an exploratory primary research and Antonio Gramsci’s theory of cultural hegemony, this dissertation argues that multiculturalism has become an unquestioned, hegemonic ideology in Singapore, resulting in the manifestations of Chinese privilege and Islamophobia. It follows this opinion by demonstrating how these cultural phenomena have exacerbated the alienation and discrimination of the Malay-Muslim community in Singapore. By complementing existing research about religious extremism with available public data about Singaporeans detained under the Internal Security Act, this dissertation further posits that the experiences of alienation and discrimination aggravate religious extremism in Singapore. It then concludes by contemplating the policy implications of its findings and possible future research opportunities.